Layer-by-Layer assembled nano-drug delivery systems for cancer treatment. (1st January 2021) - Zhang, Xinyi; Liang, Tianying; Ma, Qingming
Abstract: Nano-drug delivery systems (NDDS) are functional drug-loaded nanocarriers widely applied in cancer therapy. Recently, layer-by-layer (LbL) assembled NDDS have been demonstrated as one of the most promising platforms in delivery of anticancer therapeutics. Here, a brief review of the LbL assembled NDDS for cancer treatment is presented. The fundamentals of the LbL assembled NDDS are first interpreted with an emphasis on the formation mechanisms. Afterwards, the tailored encapsulation of anticancer therapeutics in LbL assembled NDDS are summarized. The state-of-art targeted delivery of LbL assembled NDDS, with special attention to the elaborately control over the passive and active targeting delivery, are represented. Then the controlled release of LbL assembled NDDS with various stimulus responsiveness are systematically reviewed. Finally, conclusions and perspectives on further advancing the LbL assembled NDDS toward more powerful and versatile platforms for cancer therapy are discussed.